You have 3-4 steps in an induction proof
Using 1+3+5+...+(2n-1) = n² as an example:
Step 1: Test the initial case (so for this example that is n = 1)
LHS = 1
RHS = 1² = 1
LHS = RHS hence statement is true for n = 1
All we have done here is verify the statement is correct for one particular value of n (here it is n = 1). We haven't proved it is correct for any other value of n yet.
Step 2: ASSUME the statement is true for n = k
1+3+5+...+(2k-1) = k²
Now we "pretend" the statement is correct for some random value of n. Note that we haven't proved it is correct, we've just pretended it is
Step 3: Prove the statement is true for the NEXT value of n (in this case n = k+1)
Required to prove statement is true for n = k + 1
1+3+5+...+(2k+1) = (k+1)²
LHS = 1+3+5+...+ (2k+1)
if we just peek at the second last term:
= 1+3+5+...+ (2k-1) + (2k+1)
= [1+3+5+...+ (2k-1)] + (2k+1)
What does the stuff in the brackets look like? Our ASSUMPTION from step 2!
= k² + 2k + 1
= (k + 1)²
= RHS
***IF the statement it true for n = k then the statement is true for n = k + 1
Now, IF our assumption is correct for n = k, then it is correct for n = k + 1 since we used it to prove. If our assumption is wrong for n = k, then n = k + 1 must also be wrong. But how do we know if the statement is correct or not? All we've done is pretend it was correct but we don't know for sure if it actually is correct. The key lies in looking at Step 1!
Step 4: Conclusion
Since the statement is true for n = 1 (from Step 1), then it is true for n = 1 + 1 = 2. If it is true for n = 2, then it is true for n = 2 + 1 = 3 and so on. Hence by induction the statement is true for all n integers greater than or equal to 1.
If we look at step 1, we KNOW the statement is DEFINITELY true for n = 1 as proven without having to pretend it is true. So it is true for one value of n. Now from step 3***, we said that IF it is true for one value then it is true for the next. So if n = k = 1 is true then it is also true for n = k + 1 = 1 + 1 = 2. So it is DEFINITELY TRUE for 2. Now if we make n = k = 2 this time which we know is now true, then n = k + 1 = 2 + 1 = 3 is also true. Following the inductive pattern since n = 3 is true then n = 4 is true. Since n = 4 is true then n = 5 is true and so on....